Patrol Ship Design to Guard the Natuna Seas - Suardi Huda; Amalia Ika Wulandari; Muhammad Uswah Pawara; Alamsyah; Taufik Hidayat (International Journal of Marine Engineering Innovation and Research, 2022)
Natuna is one of the regencies in the Riau Archipelago Province, the area of Natuna Regency is 224,684.59 km2 with a land area of 2,000.85 km2 and an ocean area of 222,683.74 km2. According to the Ministry of Maritime Affairs and Fisheries, Natuna occupies the first position for the purpose of exporting fishery products from the SKPT location (Integrated Marine and Fishery Centers in Small Islands and Border Areas), namely marine fisheries resources reaching more than 1 million tons per year. The extent of Natuna waters and the large potential of existing capture fisheries resources cause the Natuna waters to be included in the Fisheries Management Area (WPP 711) which is prone to illegal fishing activities. It has been proven recently that in the waters of North Natuna there are coast guard ships from foreign countries escorting fishing vessels belonging to their countries that are carrying out illegal, unreported, and unregulated fishing activities. The purpose of this research is to design a patrol ship to carry out security missions around the Natuna waters. The method used in this design is the Parent Design Approach method. This method is known in designing ships, namely by taking a comparison ship that has the same characteristics as the ship to be designed. The main dimensions of the ship obtained in this final project are Lwl = 50.2 m, B = 9.32 m, H = 4.45 m, T = 3.5 m, Vs (max) = 25 Knots, Crew = 40 Indonesian navy. Armaments used on this ship are Oto-Melara 76/62SR 76 mm, Oerlikon Millennium 35 mm, RWS Machine Gun, and SS1-V1 Kal hand rifle. 5.56 mm.